2017
DOI: 10.1103/physrevd.95.016001
|View full text |Cite
|
Sign up to set email alerts
|

Critical Schwinger pair production. II. Universality in the deeply critical regime

Abstract: We study electron-positron pair production by spatially inhomogeneous electric fields. Depending on the localization of the field, a critical point (critical surface) exists in the space of field configurations where the pair production probability vanishes. Near criticality, pair production exhibits universal properties similar to those of continuous phase transitions. We extend results previously obtained in the semi-classical (weak-field) critical regime to the deeply critical regime for arbitrary peak fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 71 publications
(127 reference statements)
3
29
0
Order By: Relevance
“…[24][25][26]. However, there are only a few cases when such exact solutions are known.It was recently shown that near criticality, pair production exhibits universal properties similar to those of continuous phase transitions [27,28]. In our terminology, this corresponds to the situation when the Klein zone is relatively small.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…[24][25][26]. However, there are only a few cases when such exact solutions are known.It was recently shown that near criticality, pair production exhibits universal properties similar to those of continuous phase transitions [27,28]. In our terminology, this corresponds to the situation when the Klein zone is relatively small.…”
mentioning
confidence: 90%
“…(23) is stronger than Eqs. (16) and (28) if the fields are weak, whereas they are equivalent if the fields are strong. For this reason, defining the scale ∆l m st in general terms, we choose the form (4).…”
Section: Introductionmentioning
confidence: 99%
“…the imaginary part of the one-loop QED effective action exhibits universal properties similar to those of continuous phase transitions [38,39]. According to our terminology, this occurs when the Klein zone is sufficiently small, as in the case of strong fields in the sharp-gradient regime.…”
Section: Sharp-gradient Configurationmentioning
confidence: 81%
“…Switching off the backreaction, i.e. ignoring the integral in (9), yields no oscillations after the external field declines to zero, with both E and n constant.…”
Section: Sauter Pulsementioning
confidence: 99%
“…For ideas to boost the pair creation rate by superposing a strong, slowly varying field with a weak but fast field, see [5,6]. ‡ For further generalizations to include spatial gradients, see [8,9]. Other setups, not necessarily using lasers, are the field in the vicinity of a superheavy atomic nucleus [10][11][12][13][14], or a superposed XFEL beam [15,16].…”
Section: Introductionmentioning
confidence: 99%